Some New Results on the Lotka-Volterra System with Variable Delay - Yangzi Hu; Fuke Wu; Chengming Huang (Abstract and Applied Analysis)
This paper discusses the stochastic Lotka-Volterra system with time-varying delay. The nonexplosion, the boundedness, and the polynomial pathwise growth of the solution are determined once and for all by the same criterion. Moreover, this criterion is constructed by the parameters of the system itself, without any uncertain one. A two-dimensional stochastic delay Lotka-Volterra model is taken as an example to illustrate the effectiveness of our result.